Educational Digital Games integrated into Remote Labs: systematic and mapping reviews - Tulha, Carinna Nunes; Carvalho, Marco Antonio Garcia de; Coluci, Vitor Rafael (Revista Brasileira de Informática na Educação, 2021)
Remote laboratories and digital games are consolidated learning technologies. Recent works have demonstrated synergistic effects when these technologies are integrated. In this work, we performed systematic and mapping reviews to determine how is the state of the art of the integration process of remote labs and educational digital games. The reviews were carried out by using interdisciplinary databases following well established reviewing protocols. We found 13 papers with the systematic review and 20 with the mapping review. These papers were organized into four groups: (1) Theoretical, (2) Proposal, (3)Prototype, (4) Validation. Our findings showed the integration of these technologies is still in the beginning, since most of the sum of works on theoretical concepts, initial propositions or prototypes is still large than the works on validated results. We found trends towards integrated learning tools based on remote laboratories and digital games but these works are scarce, spatially concentrated and, in most cases, unavailable for massive use.